The Performance of External Vertical Slats for Shading West Windows in Office Buildings - Haule, Evance Melkiory; Chaiwiwatworakul, Pipat; Chirarattananon, Surapong (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 3 (2020): July-September 2020, 2020)
In a hot climate region, the solar radiation transmitted into the building is very high throughout the year. This causes the consumption of electricity to be higher in terms of air-conditioning. The usages of shading devices are necessary to overcome the problem of glare and solar radiation. The uses of external vertical shading devices in west windows are more effective than horizontal shading devices because the sun is travelling overhead all the time.         In most office buildings, the heat reflective glasses (HR) are used to reduce the solar radiation. Therefore, this paper discusses the performance of external vertical slats with clear glass and compares the results obtained from the heat reflective glass window in west exposure. The daylighting performance was evaluated for both cases of using external vertical slats and HR in June and December to check variations. The results of the simulation showed that the application of external vertical slats always reduces energy consumption for three window to window ratio (0.3WWR, 0.6WWR and 0.9WWR) scenarios this is beneficial to the occupants. The results indicate that using the external vertical slats in the west façade achieving potential energy savings ranging between 16%– 52% less energy compared to heat reflective glass. Keywords: Solar radiation, Shading devices, External vertical slats, Heat reflective glass and Energy saving